Combination of a geolocation database access with infrastructure sensing in TV bands - Dionísio, Rogério (2016)
This paper describes the implementation and the technical specifications of a geolocation database assisted by a spectrum-monitoring outdoor network. The geolocation database is populated according to Electronic Communications Committee (ECC) report 186 methodology. The application programming interface (API) between the sensor network and the geolocation database implements an effective and secure connection to successfully gather sensing data and sends it to the geolocation database for post-processing. On the other hand, the testbed allows authorized TV white space devices to gain access to the services of the geolocation database, according to a draft implementation of Internet Engineering Task Force (IETF) Protocol to Access White Space (PAWS) Two experimental methodologies are available with the testbed: one focused on coexistence studies with commercial wireless microphones, when the testbed is used for sensing only, and another for demonstration purposes, when the testbed is also used to emulate wireless microphone signals. Overall, this hybrid approach is a promising solution for the effective use of TV white spaces and for the coexistence with digital TV broadcast signals, or dynamic incumbent systems, such as unregistered wireless microphones.